(untitled) (Journal for the Study of Religion and History (JSRH), 2025)
Chen Yuan, the president of Fu Jen Catholic University, was a famous scholar in the field of religion studies. Ying Lianzhi, a distinguished educator and philanthropist, founded Ta Kung Pao and Fu Jen Catholic University. They had been acquainted with each other for nearly ten years until Ying Lianzhi died in 1926. They collected, collated and published the Catholic works written in late Ming and early Qing periods. Chen Yuan, together with Ying Lianzhi not only promoted the academic research of Chinese Catholic history, but also participated in the localization of Chinese Catholicism actively.